Ganglioside deficiency in hypothalamic POMC neurons promotes body weight gain - Dieterle, Vanessa; Herzer, Silke; Gröne, Hermann-Josef; Nordström, Viola (International journal of obesity, 2020)
Glucosylceramide synthase (GCS; gene: UDP-glucose:ceramide glucosyltransferase (Ugcg))-derived gangliosides comprise a specific class of lipids in the plasma membrane that modulate the activity of transmembrane receptors. GCS deletion in hypothalamic arcuate nucleus (Arc) neurons leads to prominent obesity. However, it has not yet been studied how ganglioside depletion affects individual Arc neuronal subpopulations. The current study investigates the effects of GCS deletion specifically in anorexigenic pro-opiomelanocortin (POMC) neurons. Additionally, we investigate insulin receptor (IR) signaling and phosphatidylinositol-(3,4,5)-trisphosphate (PIP3) binding to ATP-dependent K+ (KATP) channels of GCS-deficient POMC neurons. We generated Ugcgf/f-Pomc-Cre mice with ganglioside deficiency in POMC neurons. Moreover, the CRISPR (clustered regulatory interspaced short palindromic repeats)/Cas9 technology was used to inhibit GCS-dependent ganglioside biosynthesis in cultured mouse POMC neurons, yielding UgcgΔ-mHypoA-POMC cells that were used to study mechanistic aspects in further detail. Proximity ligation assays (PLAs) visualized interactions between gangliosides, IR, and KATP channel subunit sulfonylurea receptor-1 (SUR-1), as well as intracellular IR substrate 2 (IRS-2) phosphorylation and PIP3. Chow-fed Ugcgf/f-Pomc-Cre mice showed a moderate but significant increase in body weight gain and they failed to display an increase of anorexigenic neuropeptide expression during the fasting-to-re-feeding transition. IR, IRS-2, p85, and overall insulin-evoked IR and IRS-2 phosphorylation were elevated in ganglioside-depleted UgcgΔ-mHypoA-POMC neurons. A PLA demonstrated that more insulin-evoked complex formation occurred between PIP3 and SUR-1 in ganglioside-deficient POMC neurons in vitro and in vivo. Our work suggests that GCS deletion in POMC neurons promotes body weight gain. Gangliosides are required for an appropriate adaptation of anorexigenic neuropeptide expression in the Arc during the fasting-to-re-feeding transition. Moreover, gangliosides might modulate KATP channel activity by restraining PIP3 binding to the KATP channel subunit SUR-1. Increased PIP3/SUR-1 interactions in ganglioside-deficient neurons could in turn potentially lead to electrical silencing. This work highlights that gangliosides in POMC neurons of the hypothalamic Arc are important regulators of body weight.
Published online: 05 June 2019
Gesehen am 26.02.2020